The role of perceived social support on physical activity participation of 6th to 8th grade students [6. - 8. Sinif Öǧrencilerinin Fiziksel Aktiviteye Katiliminda Algiladiklari Sosyal Desteǧin Rolü] - (:unkn) unknown (My University, 2013)
The purpose of this study was to investigate the role of perceived social support on 6th, 7th and 8th grade students' physical activity levels with regard to gender and school type (private versus public). In this study, both qualitative and quantitative research methodologies were applied. The participants were 266 students from one public and one private school. It is found that perceived social support seems to be an important factor on students' physical activity paterns. Participants reported that they received more social support from their peers when compared to their parents, wherein their mothers were the only significant social support provider. Results also revealed that students from the private school significantly received more social support from their family compared to students from the public school. Moreover, physically active students, especially girls, reported that they received more social support from their mothers.
Keywords: Perceived social support; Physical activity